Econometric Assessment of the Number of Youth as a Factor of the Development of Small Business in Regions - Doroshenko, Svetlana Victorovna; Shelomentsev, Andrey Gennadievich (Economy of Regions, 2019)
The article describes the results of the study of the certain factors influencing the development of small business in the Russian regions. We focused on assessing the influence of the demographic factor, namely the number of youth. This topic is relevant due to the outflow of youth from the majority of regions and the implementation of the national project for the development of business. We hypothesise there is a positive relation between the number of youth in a region and the number of small businesses there. Further, to prove our hypothesis, we aimed to confirm the interaction of two processes. Firstly, the support of youth's entrepreneurial initiatives reduces the migration mood. Secondly, the preservation of youth in a region stimulates the development of small businesses by enforcing the performance indicators of the national project. This hypothesis has not previously been tested in Russian academic papers. Using foreign and Russian studies on the problem of development factors, we divided them into three nominal groups: «classification», «single-factor» and «model». Constructing the model, we chose a combination of individual exogenous factors of small business' development in the regions: geographical, infrastructure, and financial ones. Moreover, based on the eclectic theory of entrepreneurship, we studied some supply factors: education, unemployment, and demography. We considered the population aged from 20 to 34 as an actualized demographic factor. The dependent variables were the number of small and micro businesses, the number of individual entrepreneurs, and the number of small businesses (as the sum of the first two indicators). We built separate models for each indicator. The first two models have identified the stability and confirmed the unidirectional results. Additionally, we introduced in the models a contextual factor, namely the crises of2008-2009 and 2014. The econometric assessment has shown that the number of youth positively influences the growth of small businesses and individual entrepreneurship in regions. The indicator is significant at the level of 1 %, it is stable and obvious for all model specifications.